Akibat Hukum terhadap Jual Beli Rumah Harta Bersama Pasca Perceraian - Rai Agus Dwi Ernata Putra; I Nyoman Budiartha; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2020)
A marriage in Indonesia is a matter that is considered very, very sacred which in that period of course has various consequences. Along with this period, it is not uncommon for a social conflict to become a community disease when a quarrel occurs between the two, namely divorce which will eventually spread to other problems such as childcare issues, gono-gini assets and other assets that were obtained during the marriage. . The purpose of this research is to know the status of the sale and purchase of joint property houses after divorce and to know the legal consequences of buying and selling joint property after divorce against third parties. This study uses a normative method with a statutory approach, namely by reviewing laws, books and various opinions of scholars and experts. So that the results of this study reveal that the assets between the husband and wife have been regulated and stipulated in Article 119 of the Civil Code (KUH Perdata) which explains that starting from the validity of a marriage, it also applies the unanimity of assets as long as it is not There are other rules that state and regulate their assets which are tied to marriage, which were made before the marriage took place.